Development of Electronic Student Worksheets (E-LKPD) Assisted by Wizer.Me on Gastropods Sub Material - Mayasari Mayasari; Afreni Hamidah; Agus Subagyo (Jurnal Penelitian Pendidikan IPA, 2023)
One of the teaching materials that can improve student competence in cognitive aspects and student learning activities is Electronic Worksheets. Gastropods is a sub-material on the diversity of living things which is only discussed in general by the teacher so that the introduction of Gastropods to students is still lacking. To introduce and make learning more interesting, researchers provide an alternative E-LKPD assisted by wizer.me which displays descriptions, examples, pictures of Gastropods and activities that involve students directly with the natural surroundings. This research is a Research and Development (R&D) development research using the ADDIE development model which consists of Analysis, Design, Development, Implementation and Evaluation. The type of research data is qualitative and quantitative. Collecting research data using media and material validation questionnaires, perceptions of teachers and students. The test subjects in this study were 1 biology teacher, class XI students at Al-Falah Islamic High School, Jambi City, who were divided into small groups consisting of 6 people and large groups consisting of 23 people. The results of the research on the validation of material experts obtained a percentage of 83.33% in the very good category. Furthermore, the results of the validation of media experts obtained a percentage of 85% in the very good category. The results of the teacher's perception of 95% in the very good category, the results of the small group test obtained a percentage of 94.72% in the very good category and the large group test obtained a percentage of 85.94 in the very good category. Thus the E-LKPD assisted by wizer.me on the developed Gastropods sub-material is suitable for use as teaching materials that can support the learning process based on the results of validation of material experts, media experts, teacher responses and student responses